Characteristics and Outcomes of Children with Clinical History of Atopic Versus Non-atopic Asthma Admitted to a Tertiary Pediatric Intensive Care Unit - Causey, Jamie (Open Respir Med J, 2018)
BACKGROUND: Children admitted to the Pediatric Intensive Care Unit (PICU) with status asthmaticus have variable clinical courses, and predicting their outcomes is challenging. Identifying characteristics in these patients that may require more intense intervention is important for clinical decision-making. OBJECTIVE: This study sought to determine the characteristics and outcomes, specifically length of stay and mortality, of atopic versus non-atopic asthmatics admitted to a PICU with status asthmaticus. METHODS: A retrospective study was conducted at a children’s hospital from November 1, 2008 to October 31, 2013. A total of 90 children admitted to the PICU were included in the analysis. Patients were divided into two groups based on the presence of specific historical data indicative of a clinical history of atopy. Children were considered to be atopic if they had a parental history of asthma, a personal history of eczema, or a combined history of wheezing (apart from colds) and allergic rhinitis (diagnosed by a medical provider). The median hospital Length Of Stay (LOS), PICU LOS, cardiopulmonary arrest, and mortality were compared between atopic and non-atopic asthma groups. Regression models were used to estimate the LOS stratified by atopic or non-atopic and by history of intubation in present hospitalization. RESULTS: Median hospital LOS for atopic children was 5.9 days (IQR of 3.8-8.7) and 3.5 days (IQR of 2.2-5.5) for non-atopic asthmatics (z = 2.9, p = 0.0042). The median PICU LOS was 2.5 days (IQR 1.4-6.1) for atopic asthmatics and 1.6 days (IQR 1.1-2.4) for non-atopic asthmatics (z = 2.5, p = 0.0141). The median LOS was significantly higher for atopic intubated patients compared to non-atopic intubated patients (p=0.021). Although there was an increased tendency towards intubation in the atopic group, the difference was not significant. There was no significant difference in cardiopulmonary arrest or mortality. CONCLUSION: A clinical history of atopic asthma in children admitted to the PICU with status asthmaticus was associated with longer length of stays The longest LOS was observed when atopic patients required intubation.